Structural equation modeling of the relationship between posttraumatic growth and psychosocial factors in women with breast cancer. Issue 8 (7th November 2016) - Tomita, Makiko; Takahashi, Miyako; Tagaya, Nobumi; Kakuta, Miyako; Kai, Ichiro; Muto, Takashi
Abstract: Objective: Posttraumatic growth (PTG) is a positive psychological change occurring after struggling with a highly challenging experience. The purposes of this study were to investigate how women's demographic and clinical characteristics as well as psychosocial factors are associated with PTG and to reveal the influence of PTG on depressive symptoms. Methods: Participants were 157 women with breast cancer (BC) who attended a breast oncology clinic at a university hospital in Japan. The questionnaire included demographic and clinical characteristics, social support, coping strategies, depressive symptoms, and PTG. Structural equation modeling was conducted. Results: Coping was directly related to PTG, and social support and having a religion were partially related to PTG. There was a moderate association between social support and coping. PTG mediated the effect of coping on depressive symptoms. PTG as well as a high level of perceived social support and using positive coping decreased depressive symptoms, whereas using self‐restraining coping increased depressive symptoms. Conclusion: This study indicated the role of coping strategies and social support in enhancing PTG in Japanese women with BC. Furthermore, perceived social support, a positive approach coping style, and PTG may reduce depressive symptoms. Our results suggest that health care professionals should consider whether patients receive enough support from others, and whether the patients are using the appropriate coping style to adapt to stressors associated with the diagnosis and treatment of BC.